PENGARUH PERILAKU KEWIRAUSAHAAN TERHADAP PENDAPATAN USAHA BBM ECERAN DI KECAMATAN TELUK DALAM KABUPATEN NIAS SELATAN - Regina S. M. Gaho (Pareto: Jurnal Riset Bisnis dan Manajemen, 2022)
The scope of this research is a study of the influence of entrepreneurial hebavior on retail fuel business income in Telukdalam District, South Nias Regency. The purpose of this study was to determine the effect of entrepreneurial hebavior on income.the research method used is simple linear regression analysis through research instrument test, classical assumption test, and hypothesis testing (t test and determination test). The population and sample in this study were 34 retailers where the technique sampling is taking randomly. The results of a simple linear regression test with the equation Y=11,540+0,694X, obtaining a value of b0=11,540 is the value of income (Y) when entrepreneurial behavior (X) is normal. For b1=0,694 is the value where every increase in entrepreneurial behavior (X) by 1 unit will increase the income (Y) of the retail fuel business in Telukdalam District, South Nias Regency by 0,694 unit. partial hyphotesis for entrepeneurial hebavior has a value of thitung 6,450>ttabel 1,694 with a df: n-k-1 (34-1-1)=32. This research can be concluded that entrepreneurial hebavior has a ppositive effect on income retail fuel business in Telukdalam District, South Nias Regency.